Effects of Medium- and Short-Chain Fatty Acids on Growth Performance, Nutrient Digestibility, Gut Microbiota and Immune Function in Weaned Piglets - Shuang Dong; Nan Zhang; Jihua Wang; Yu Cao; Lee J. Johnston; Yongxi Ma (Animals)
The aim of this study was to investigate the combination effects of α-glycerol monolaurate (GML) and glyceryl tributyrate (TB) on growth performance, nutrient digestibility, gut microbiota, and immune function in weaned piglets. A total of 120 weaned piglets with an average body weight (BW) of 6.88 kg were randomly allocated to one of the three dietary treatments: (1) CON: a basal diet; (2) 0.1%: a basal diet with 0.1% MSCFA (GML/TB = 1:1); (3) 0.2%: a basal diet with 0.2% MSCFA (GML/TB = 1:1). The experiment lasted 28 days. There were no differences on average daily growth (ADG), average daily feed intake (ADFI), and feed conversion ratio (FCR). Supplementation with 0.1% MSCFA increased apparent total tract digestibility (ATTD) of crude protein (CP) and gross energy (GE, p < 0.05) on d 14 and increased GE (p < 0.05) on d 28 compared with the CON group. The ATTD of dry matter (DM), organic matter (OM) and crude protein (CP) of piglets supplemented with 0.1% MSCFA was higher (p < 0.05). Compared with the CON group, supplementation with 0.1% MSCFA increased immunoglobulin M (IgM) concentration, decreased interleukin-6 (IL-6) content (p < 0.05) on d 14 and decreased malonaldehyde (MDA), interleukin-1beta (IL-1β), IL-6 concentrations (p < 0.05) on d 28. Supplementation with 0.1% MSCFA increased total antioxidant capacity (T-AOC) concentration (p < 0.05), decreased GSH-Px, MDA content (p < 0.05) in jejunum compared with the CON group. Moreover, supplementation with MSCFA increased the activity of duodenal lipase (p < 0.05) and the abundance of firmicutes and decreased the abundance of proteobacteria compared with the CON group. Overall, supplementation with MSCFA can improve nutrient digestibility, enhance immunity and antioxidant capacity, and improve the intestinal health of piglets. The combined use of MSCFA is a nutrition regulation strategy worthy of further exploration in modern animal husbandry.